High-strength PETG copolyester and preparation method thereof

By introducing modified nanocellulose into PETG copolyester, the problem of PETG materials prone to creep under long-term stress is solved, and its creep resistance and mechanical properties are significantly improved.

CN118480254BActive Publication Date: 2025-04-25JIANGSU YIERMAN NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410727566.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-06
Publication Date
2025-04-25
Estimated Expiration
2044-06-06

AI Technical Summary

Technical Problem

PETG materials are prone to creep when they are subjected to external stress for a long time, resulting in a degradation in performance when used in photovoltaic panel frames or bracket structures.

Method used

By introducing modified nanocellulose, the crystallinity and compatibility of PETG copolyester are improved and its creep resistance is enhanced. Modified nanocellulose is modified by 4-hydroxybenzoic acid graft to increase compatibility with PETG and improve crystallinity.

Benefits of technology

It significantly improves the creep resistance and comprehensive mechanical properties of PETG materials, and extends its service life under high stress environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of new materials, and specifically proposes a high-strength PETG copolyester and a preparation method thereof, wherein the raw materials of the high-strength PETG copolyester include terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and modified nanocellulose, and the modified nanocellulose is prepared by reacting 4-hydroxybenzoic acid and nanocellulose. By adopting the modified nanocellulose, the creep resistance of the PETG copolyester can be significantly improved, so that the PETG copolyester can effectively maintain shape and dimensional stability under long-term stress, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to a high-strength PETG copolyester and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate-1,4-cyclohexanedimethanol, referred to as PETG, is a new type of amorphous polyester material. It is made of terephthalic acid, ethylene glycol and 1,4-cyclohexanedimethanol through ester exchange reaction. Compared with PET and PCT, PETG has primary thermoforming properties, good toughness, weather resistance, good processing properties, and is more environmentally friendly due to its unique chemical structure.

[0003] PETG has a wide range of applications, including plates, sheets, high-performance shrink films, bottles, and profiles. It is also widely used in the photovoltaic industry, such as the frame or support structure of photovoltaic panels. However, the amorphous area of ​​PETG accounts for a relatively high proportion, which also leads to a relatively large degree of freedom of movement of its molecular chain. Photovoltaic panels are usually installed in flat areas with good sunshine, which means that they need to withstand large wind loads for a long time. This long-term stress also makes the frame or support lamp made of it prone to creep. Improving its anti-creep performance has become a technical problem that needs to be solved urgently. Summary of the invention

[0004] In view of this, the present invention proposes a high-strength PETG copolyester, aiming to improve the creep resistance of the PETG copolyester by optimizing and improving the raw materials of the PETG copolyester.

[0005] The technical solution of the present invention is achieved as follows: the present invention provides a high-strength PETG copolyester, the raw materials of which include: phthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and modified nanocellulose, and the modified nanocellulose is prepared by reacting 4-hydroxybenzoic acid and nanocellulose.

[0006] The creep resistance of PETG is relatively poor, mainly due to its molecular structure and polymer properties. Due to the introduction of 1,4-cyclohexanedimethanol into the PETG molecular chain, its molecular chain is softer than ordinary PET. This flexible molecular chain is more likely to slip and rearrange under stress, leading to creep; secondly, there are more amorphous regions in PETG, and the interchain force is relatively weak, which makes it easier for the molecular chains to move relative to each other under long-term load, leading to creep. Nanocellulose has high crystallinity and high specific surface area, and can be used as an efficient crystallization promoter. When it is mixed with PETG monomer to prepare PETG, it can significantly improve the crystallinity of PETG. However, due to the presence of surface hydroxyl groups, conventional nanocellulose has strong hydrophilicity and poor compatibility with the PETG matrix. This will cause the introduction of nanocellulose to form interface defects in the PETG matrix, which will not only not increase the creep resistance of PETG under long-term stress, but will lead to a decrease in its mechanical properties in all aspects. After the nanocellulose is grafted with 4-hydroxybenzoic acid, the chemical properties of the nanocellulose change, the compatibility with PETG is increased, and the problem of decreased mechanical properties caused by the hydroxyl groups in the nanocellulose is overcome. At the same time, the crystallinity of PETG is improved, and its creep resistance is enhanced. At the same time, the grafted 4-hydroxybenzoic acid also has a high degree of crystallinity, which can induce the PETG molecular chains to arrange regularly on the cellulose surface, forming more crystalline areas, and improving the crystallinity and creep resistance of the material. These advantages are not possessed by unmodified nanocellulose.

[0007] In some embodiments, the preparation method of modified nanocellulose includes: mixing nanocellulose, 4-hydroxybenzoic acid, p-toluenesulfonic acid and ethanol solution, heating to 60-100° C., stirring for 4-6 hours, filtering the reaction system, washing the filter cake with water, and drying to obtain modified nanocellulose.

[0008] In the above embodiment, p-toluenesulfonic acid is used as a catalyst. Under heating conditions, the carboxyl group of 4-hydroxybenzoic acid reacts with the hydroxyl group on the surface of nanocellulose to form an ester bond, thereby introducing an aromatic structure to the surface of nanocellulose. The grafted modified nanocellulose is more compatible with PETG, and its thermal stability and mechanical strength are improved. The water washing operation of the filter cake is used to remove excess solvent and catalyst, as well as unreacted 4-hydroxybenzoic acid.

[0009] In some embodiments, the mass ratio of nanocellulose:4-hydroxybenzoic acid:p-toluenesulfonic acid is 100:(5-20):(0.5-2).

[0010] In some embodiments, the ethanol solution has a concentration of 65% vol.

[0011] In some embodiments, the molar ratio of terephthalic acid:1,4-cyclohexanedimethanol:ethylene glycol is 1:(0.1-0.5):1.

[0012] In some embodiments, the amount of nanocellulose used is 2%-10% of the sum of the mass of phthalic acid, 1,4-cyclohexanedimethanol, and ethylene glycol.

[0013] In a second aspect, the present invention also provides a method for preparing the above-mentioned high-strength PETG copolyester, comprising the following steps: mixing terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and modified nanocellulose, heating to 270-290°C, keeping the mixture warm for 3-5 minutes, and obtaining the high-strength PETG copolyester after molding.

[0014] Blending modified nanocellulose with PETG monomers can form stronger interactions between PETG molecular chains, improve the crystallinity of the material, and enhance its mechanical properties. At the same time, the aromatic ring structure of 4-hydroxybenzoic acid helps to improve the thermal stability and durability of the material. The resulting high-strength PETG can exhibit good creep resistance under long-term external stress.

[0015] In some embodiments, after molding, the process further includes: heating to 90°C and keeping warm for 5-10 minutes, then cooling to 80°C at 5°C / min, keeping warm for 10-30 minutes, then cooling to 60°C at 5°C / min, keeping warm for 10-30 minutes, then cooling to 30°C at 2°C / min to obtain high-strength PETG copolyester.

[0016] Through the return process in the above embodiment, the crystallinity of the modified cellulose and PETG blend can be effectively improved, thereby improving its creep resistance and other mechanical properties.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The invention effectively solves the problem of poor creep resistance of traditional PETG materials by introducing modified nanocellulose, significantly improves the comprehensive performance of the materials, and provides a new technical approach for the development of high-performance polyester materials. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0021] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0022] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0023] Example 1

[0024] This embodiment provides a PETG copolyester sheet with high creep resistance

[0025] PETG copolyester sheet preparation:.

[0026] 166 g of terephthalic acid, 14.4 g of 1,4-cyclohexanedimethanol, 62 g of ethylene glycol and 4.8 g of modified nanocellulose were weighed respectively, mixed and heated to 270°C, and kept warm for 5 minutes. The molten material was passed into a single-screw extruder, extruded into a flat die, and cooled to obtain a PETG copolyester sheet.

[0027] The preparation method of the modified nanocellulose comprises: weighing 100g of nanocellulose, 5g of 4-hydroxybenzoic acid and 0.5g of p-toluenesulfonic acid respectively, adding them into 200ml of 65%vol ethanol solution, heating to 60°C, stirring and treating for 6h, then filtering, washing the filter cake with clean water, and drying to obtain the modified nanocellulose.

[0028] Example 2

[0029] This embodiment provides a PETG copolyester sheet with high creep resistance

[0030] PETG copolyester sheet preparation:.

[0031] 166 g of terephthalic acid, 72 g of 1,4-cyclohexanedimethanol, 62 g of ethylene glycol and 30 g of modified nanocellulose were weighed respectively, mixed and heated to 270°C, and kept warm for 5 minutes. The molten material was passed into a single-screw extruder, extruded into a flat die, and cooled to obtain a PETG copolyester sheet.

[0032] The preparation method of the modified nanocellulose comprises: weighing 100g of nanocellulose, 5g of 4-hydroxybenzoic acid and 0.5g of p-toluenesulfonic acid respectively, adding them into 200ml of 65%vol ethanol solution, heating to 60°C, stirring and treating for 6h, then filtering, washing the filter cake with clean water, and drying to obtain the modified nanocellulose.

[0033] Example 3

[0034] This embodiment provides a PETG copolyester sheet with high creep resistance

[0035] PETG copolyester sheet preparation:.

[0036] 166 g of terephthalic acid, 14.4 g of 1,4-cyclohexanedimethanol, 62 g of ethylene glycol and 4.8 g of modified nanocellulose were weighed respectively, mixed and heated to 270°C, and kept warm for 5 minutes. The molten material was passed into a single-screw extruder, extruded into a flat die, and cooled to obtain a PETG copolyester sheet.

[0037] The preparation method of the modified nanocellulose comprises: weighing 100g of nanocellulose, 20g of 4-hydroxybenzoic acid and 2g of p-toluenesulfonic acid respectively, adding them into 200ml of 65%vol ethanol solution, heating to 100°C, stirring and treating for 4h, then filtering, washing the filter cake with clean water, and drying to obtain the modified nanocellulose.

[0038] Example 4

[0039] This embodiment provides a PETG copolyester sheet with high creep resistance

[0040] PETG copolyester sheet preparation:.

[0041] 166 g of terephthalic acid, 14.4 g of 1,4-cyclohexanedimethanol, 62 g of ethylene glycol and 4.8 g of modified nanocellulose were weighed respectively, mixed and heated to 290°C, and kept warm for reaction for 3 minutes. The molten material was passed into a single-screw extruder, extruded into a flat die, and cooled to obtain a PETG copolyester sheet.

[0042] The preparation method of the modified nanocellulose comprises: weighing 100g of nanocellulose, 5g of 4-hydroxybenzoic acid and 0.5g of p-toluenesulfonic acid respectively, adding them into 200ml of 65%vol ethanol solution, heating to 60°C, stirring and treating for 6h, then filtering, washing the filter cake with clean water, and drying to obtain the modified nanocellulose.

[0043] Example 5

[0044] This embodiment provides a PETG copolyester sheet with high creep resistance

[0045] PETG copolyester sheet preparation:.

[0046] 166 g of terephthalic acid, 14.4 g of 1,4-cyclohexanedimethanol, 62 g of ethylene glycol and 4.8 g of modified nanocellulose were weighed respectively, mixed and heated to 270°C, kept warm for reaction for 5 minutes, the molten material was passed into a single-screw extruder, extruded into a flat mold, and cooled to obtain a PETG copolyester sheet. The polyester sheet was placed in an insulation box and heated to 90°C for insulation treatment for 5-10 minutes, then cooled to 80°C at 5°C / min, kept warm for 10-30 minutes, then cooled to 60°C at 5°C / min, kept warm for 10-30 minutes, and then cooled to 30°C at 2°C / min to obtain a high-strength PETG copolyester sheet.

[0047] The preparation method of the modified nanocellulose comprises: weighing 100g of nanocellulose, 5g of 4-hydroxybenzoic acid and 0.5g of p-toluenesulfonic acid respectively, adding them into 200ml of 65%vol ethanol solution, heating to 60°C, stirring and treating for 6h, then filtering, washing the filter cake with clean water, and drying to obtain the modified nanocellulose.

[0048] Comparative Example 1

[0049] This comparative example provides a conventional PETG copolyester sheet

[0050] PETG copolyester sheet preparation:.

[0051] 166 g of terephthalic acid, 14.4 g of 1,4-cyclohexanedimethanol and 62 g of ethylene glycol were weighed respectively, mixed and heated to 270°C, and kept warm for reaction for 5 minutes. The molten material was passed into a single-screw extruder, extruded into a flat die, and cooled to obtain a PETG copolyester sheet.

[0052] Comparative Example 2

[0053] This embodiment provides a PETG copolyester sheet with high creep resistance

[0054] PETG copolyester sheet preparation:.

[0055] 166 g of terephthalic acid, 14.4 g of 1,4-cyclohexanedimethanol, 62 g of ethylene glycol and 4.8 g of nanocellulose were weighed respectively, mixed and heated to 270°C, and kept warm for 5 minutes. The molten material was passed into a single-screw extruder, extruded into a flat die, and cooled to obtain a PETG copolyester sheet.

[0056] The PETG copolyester sheets prepared in the embodiment and the comparative example were processed into dumbbell-shaped sheets of the same size, and a constant tensile stress test was performed at 40° C. using a tensile testing machine. The deformation was measured using a high-precision video extensometer. The strain was measured 1 minute and 100 hours after the stress was applied, respectively. The tensile stress was 50% of the breaking strength of the conventional PETG dumbbell-shaped sheet. The data results are shown in the following table:

[0057] Grouping 1min strain / % 100h strain / % Example 1 0.3 0.5 Example 2 0.2 0.5 Example 3 0.3 0.4 Example 4 0.3 0.5 Example 5 0.2 0.3 Comparative Example 1 1.2 2.3 Comparative Example 2 0.3 2.6

[0058] It is not difficult to see from the above data that the PETG copolyester sheet prepared in the embodiment group has a significant creep resistance compared to the conventional PETG copolyester sheet of the comparative example, and it can be seen from the data comparison of Example 1 and Example 5 that after annealing, the creep resistance of the PETG copolyester sheet is further improved, considering that the annealing step reduces the amorphous region in the PETG copolyester again. It can be seen from the data comparison of Comparative Example 2 and Example 1 that after adding nanocellulose, the creep resistance of the PETG copolyester sheet can be improved in a short time, but under long-term stress, the defect factors brought by nanocellulose in the PETG copolyester will gradually reduce its creep resistance, even lower than the PETG copolyester sheet without nanocellulose blending.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-strength PETG copolyester, characterized in that: The raw materials of the high-strength PETG copolyester include terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and modified nanocellulose. The preparation method of the modified nanocellulose includes: mixing nanocellulose, 4-hydroxybenzoic acid, p-toluenesulfonic acid and ethanol solution, heating to 60-100°C, keeping warm and stirring for 4-6 hours, filtering the reaction system, washing the filter cake with water, and drying to obtain the modified nanocellulose, the mass ratio of nanocellulose: 4-hydroxybenzoic acid: p-toluenesulfonic acid is 100: (5-20): (0.5-2), and the concentration of the ethanol solution is 65%vol.

2. The high-strength PETG copolyester according to claim 1, characterized in that The molar ratio of terephthalic acid:1,4-cyclohexanedimethanol:ethylene glycol is 1:(0.1-0.5):

1.

3. The high-strength PETG copolyester according to claim 1, characterized in that The amount of modified nanocellulose used is 2%-10% of the sum of the mass of phthalic acid, 1,4-cyclohexanedimethanol and ethylene glycol.

4. The method for preparing the high-strength PETG copolyester described in any one of claims 1 to 3, characterized in that: The steps include: Terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and modified nanocellulose are mixed and heated to 270-290°C, kept warm for 3-5 minutes, and high-strength PETG copolyester is obtained after molding.

5. The preparation method of high-strength PETG copolyester as claimed in claim 4, characterized in that, After molding, the process further includes: heating to 90°C and heat preservation for 5-10 minutes, then cooling to 80°C at 5°C / min, heat preservation for 10-30 minutes, then cooling to 60°C at 5°C / min, heat preservation for 10-30 minutes, then cooling to 30°C at 2°C / min, to obtain high-strength PETG copolyester.

Citation Information

Patent Citations

  • Hydrophilic polyester fiber modified by cellulose nanocrystal and preparation method thereof

    CN104404647A

  • Long-chain branched PETG copolyester and preparation method thereof

    CN113929886A